Radial Anisotropy in East Asia From Multimode Surface Wave Tomography. Issue 7 (19th July 2021) - Witek, M.; Chang, S.‐J.; Lim, D. Y.; Ning, S.; Ning, J.
Abstract: We present a model of radial anisotropy in the crust and upper mantle of East Asia from a combination of new group velocity measurements and previously published surface wave dispersion data sets. Our combined data set ranges 5–375 s period and contains dispersion data up to the fifth overtone. We directly relate the data to variations in isotropic and radially anisotropic shear wave crustal and mantle structure via surface wave ray theory applied to a prior 3‐D reference model. Our isotropic S‐velocity model shares high correlations with previous studies, including a model derived from a full waveform inversion methodology. The short period dispersion measurements in our data set allow us to resolve crustal structure without the need for crustal corrections, and as a result, our radial anisotropy model has significant differences with previous studies. We find strong positive radial anisotropy ( ξ  > 1) across the entire region in the middle to lower crust and uppermost mantle. We perform a cluster analysis and find high levels of radial anisotropy ( ξ  > 1.12) in the lithospheric mantle of the back‐arc basin and in collisional belts, while low levels of radial anisotropy ( ξ  ∼ 1.04) are found in the mantle wedge of NE Japan and in the mantle upwelling under Mt. Baekdu. High radial anisotropy is found in the lower crust in regions that experienced continental rifting and lithospheric thinning, while the lowest crustal radial anisotropy is found in stable cratons. Plain Language Summary: The two types of surface waves, Rayleigh and Love, will travel with different speeds than expected as a result of "radial anisotropy, " where the Earth responds differently to horizontal motions as opposed to vertical motions. This usually happens as a result of tectonic processes that deform Earth materials, so that observations of radial anisotropy can give us important information on how materials are flowing or deforming in the Earth. In this study, we make new measurements of Rayleigh and Love wave speeds and combine them with previously published data sets in order to produce a model of the radial anisotropy in East Asia. We find that the Love waves are traveling anomalously faster than the Rayleigh waves throughout the area, and regional variations in the strength of the anisotropy can be tied to active versus stable tectonics, the direction of mantle flow, and possibly the water content. For example, we find high levels of radial anisotropy in the East Sea (Sea of Japan), which was formed as the Japanese islands rifted away from the Eurasian continent. We find weak radial anisotropy underneath Mt. Baekdu, a large intraplate volcano, which we interpret as being due to hydrous material upwelling from the mantle. Key Points: We construct a model of radial anisotropy in East Asia using multimode surface wave dispersion measurements with periods of 5–375 s We find positive radial anisotropy across nearly the entire region with a peak in the lower crust and uppermost mantle We use cluster analysis to quantify regional variations in the radial anisotropy and find correlations with recent and past tectonics